Pengaruh Persepsi Kegunaan, Persepsi Kemudahan, Faktor Sosial, Kualitas Pelayanan Fiskus, dan Dampak Penggunaan terhadap Minat menggunakan E-Filling: Studi Kasus Wajib Pajak Orang Pribadi di KPP Surakarta - Arum Putri Utami; Eskasari Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the effect of perceived usefulness, perceived ease of use, social factors, tax officer service quality, and usage impact on individual taxpayers’ intention to use e-filing at the Surakarta Primary Tax Office. A quantitative method with purposive sampling was applied to 110 respondents, and data were analyzed using multiple linear regression. The simultaneous test revealed that all independent variables significantly affected the intention to use e-filing (F = 38.816; Sig. = 0.000). The partial test showed that perceived ease of use (β = 0.321; Sig. = 0.000), tax officer service quality (β = 0.249; Sig. = 0.003), and usage impact (β = 0.372; Sig. = 0.001) had a significant positive effect, while perceived usefulness (β = -0.073; Sig. = 0.535) and social factors (β = 0.040; Sig. = 0.360) had no significant effect. The coefficient of determination indicated an Adjusted R² of 0.656, meaning that 65.6% of the variation in intention to use e-filing was explained by the independent variables. These results highlight the critical role of system ease of use, tax officer service quality, and tangible benefits in promoting e-filing adoption.